Pengaruh Etika Profesi Terhadap Kualitas Audit (Literature Review Audit) - Nabilla Farrely Rachmaputri; Azizah Rahmi; Pingki Rosalia; Trinandari Prasetya Nugrahanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
There are still audit results of poor quality which can be seen from previous financial cases involving public accountants. This article reviews the factors that influence Audit Quality, namely Professional Ethics. A study of auditing literature. The aim of this article is to build a hypothesis of the influence between variables for use in further research. The results of this literature review article are that professional ethics influences audit quality.